121 ADMINISTRASI PENYULUHAN PERTANIAN PADA KELOMPOK TANI DI KECAMATAN TABUKAN UTARA KABUPATEN KEPULAUAN SANGIHE - Virginia Mauren Rambitan; Benu Olfie L. S.; Ellen G., Tangkere (AGRI-SOSIOEKONOMI, 2016)
This study aims to determine the condition of the agricultural extension services administrative completeness of of farmer groups in the Sub-district of North Tabukan, Sangihe Islands District. The study lasted for 3 (three) months starting from January 1 to April 1 in 2016. Sampling method on two farmer groups in Tabukan North Sub-district done by purposive sampling. The first farmers group office located in Talolang Village near to the office of BP3K and the second farmer group located in Lenganeng Village far from BP3K. The asumption of this research is the farmer group near BP3K office more easily and quickly to obtain information from the agriculture extension service officer, than the farmer groups away from BP3K office. Data collection method in this study is survey method. The data used are primary data obtained from interviews, based on a list of questions, with the core committee Farmers Group (Chairman, Secretary, and Treasurer). The analysis method used in this research is qualitative descriptive analysis using criteria 1 (No Good), 2 (less good), 3 (Good). Data generated to determine the completeness of the administrative and financial administration at the farmer groups. The results of the study on two groups of farmers which Farmers Group Sengkanaung in Talolang Village and farmer groups Lestari 2 in Lenganeng Village shows that administrative of activities and financial administration of farmer groups Lestari 2 Lenganeng all fittings administration books categorized good (3) because of the activity, together with the board members, and members of the extension of farmer groups in conducting all activities. Administrative and financial administration in farmer groups Sengkanaung in Talolang Village not go well and not considered either (1) because there is no cooperation among the members of farmer groups, as well as between members of the farmer group with the agricultural extension services officer, as well as lack of knowledge and lack of guidance and advocacy for farmers' groups about the completeness of the administrative and financial administration. This conclude that the distance of location between farmer group office and the office of BP3K tend not affect the completeness of the administrative and financial work.